2015
DOI: 10.1007/s10886-015-0599-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Floral Scent Variation of Penstemon digitalis

Abstract: Variability in floral volatile emissions can occur temporally through floral development, during diel cycles, as well as spatially within a flower. These spatiotemporal patterns are hypothesized to provide additional information to floral visitors, but they are rarely measured, and their attendant hypotheses are even more rarely tested. In Penstemon digitalis, a plant whose floral scent has been shown to be under strong phenotypic selection for seed fitness, we investigated spatiotemporal variation in floral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 70 publications
3
45
0
Order By: Relevance
“…But we might also expect the past and current environmental conditions in which a plant is growing to influence its floral volatiles (e.g., Majetic et al, 2008, 2009a). Additionally, floral volatiles of an individual might change over the course of a day, over the lifetime of a flower (e.g., after ovules within a flower become fertilized), over the flowering season of an individual, or over the lifetime of a plant individual (e.g., Schiestl et al, 1997; Burdon et al, 2015). There may be interactions between typical temporal rhythms of floral volatile production and composition of a plant and the environmental conditions that it is experiencing, but this is poorly understood.…”
Section: Future Directionsmentioning
confidence: 99%
“…But we might also expect the past and current environmental conditions in which a plant is growing to influence its floral volatiles (e.g., Majetic et al, 2008, 2009a). Additionally, floral volatiles of an individual might change over the course of a day, over the lifetime of a flower (e.g., after ovules within a flower become fertilized), over the flowering season of an individual, or over the lifetime of a plant individual (e.g., Schiestl et al, 1997; Burdon et al, 2015). There may be interactions between typical temporal rhythms of floral volatile production and composition of a plant and the environmental conditions that it is experiencing, but this is poorly understood.…”
Section: Future Directionsmentioning
confidence: 99%
“…Of these, the furanoid linalool oxides may give rise to 16 possible stereoisomeric aldehydes and alcohols, collectively known as 'lilac compounds', owing to their discovery in the floral scent of Syringa vulgaris [(13; see 52)]. Lilac compounds attract specific functional groups of pollinators, such as noctuid moths [14,15] and long tongued fungus gnats [16 ] in different floral contexts.…”
Section: Which Linalool? a Pair Of Enantiomers And Their Many Derivatmentioning
confidence: 99%
“…One recent study demonstrated that variation in floral scent was significantly associated with seed fitness in a day-blooming, bee pollinated plant, Penstemon digitalis, identifying (S)-(+)-linalool as the target of phenotypic selection [51]. Further analyses identified the nectar spur as the source of this VOC [52], suggesting that (S)-(+)-linalool might function as an honest indicator of the presence of nectar, or might enhance floral constancy by pollinators, or might protect nectar from microbial infestation. Floral constancy is likely to result from a learned association of the consistent relationship between nectar availability and linalool, either as a scent or a flavor.…”
Section: Mixed Messages: Floral Signals and Cues In A Whole-plant Conmentioning
confidence: 99%
“…Whereas colored bracts or petals are mostly large‐sized to attract flower visitors from some distance, color patterns of the petals and other flower organs are small and more important for orientation at close range. This visual color pattern is paralleled by an olfactory, gustatory and tactile pattern (Burdon, Raguso, Kessler, & Parachnowitsch, ). Studies of flower odor chemistry suggest that nectar and pollen rewards frequently differ in the quantity and composition of volatile compounds compared to other floral tissues, and that such within‐flower spatial variation may function as odor guides to direct pollinators to nectar (Dötterl & Jürgens, ) or pollen rewards (Bergström et al., ; Dobson, Danielson, & Van Wesep, ).…”
Section: Introductionmentioning
confidence: 98%